Numerical research of heat transfer in gas heat exchanger; MATEC Web of Conferences; Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment - Khomutov E. O. Eugene (2015, 2015)
Title screen